Carbon storage and sequestration of five planting patterns of Picea crassifolia plantations in Qilian mountains - Shangguan, Yaoyao; Zhao, Hu; Zhang, Zhengzhong; Xu, Erwen; Lv, Dong; Wang, Yanxia; Zhao, Xingpeng; Wei, Na; Chen, Gang; Liu, Jianhai; Wei, Xingyu; Gao, Zhiwen; et al. (Frontiers in Earth Science, 2025)
Forest plantations play a critical role in mitigating climate change, with their carbon storage and sequestration capacity significantly influenced by planting patterns. This study focuses on Picea crassifolia plantations in the shallow mountainous region of the Qilian Mountains, aiming to investigate the effects of five planting patterns (pure forests, mixed forests, and uneven-aged forests) on vegetation and soil organic carbon (SOC) dynamics. The research provides a scientific basis for optimizing forest management strategies in arid and semi-arid regions. Fifteen sample plots were established in the Qilian Mountains, Gansu Province, covering five planting patterns: pure forests with 1.5 × 1.5 m (P1.5) and 2 × 2 m (P2) spacing, uneven-aged pure forests (PX), mixed forests of P. crassifolia and Pinus sylvestris var. mongholica (PC), and mixed forests of P. crassifolia, P. sylvestris, and Caragana korshinskii (PPC). Vegetation biomass (tree height, DBH, crown width) and soil samples (0 – 80 cm depth) were collected. Carbon content was determined using the potassium dichromate oxidation method, and carbon stocks were estimated using national biomass models. Statistical analyses (one-way ANOVA) and membership function evaluation were applied to assess carbon sink potential. Results showed that: 1. Planting spacing: The 2 × 2 m pure forest (P2) exhibited higher vegetation-layer carbon storage (10 t·ha−1) compared to the 1.5 × 1.5 m pure forest (P1.5, 5 t·ha−1). 2. Age heterogeneity: The uneven-aged pure forest (PX) showed the highest vegetation-layer carbon storage (6.61 t·ha−1), but its total carbon stock (106.98 t·ha−1) was slightly lower than P2 (111.08 t·ha−1) due to P2’s superior SOC content in deeper soil layers (13.64 g·kg−1 at 60–80 cm). 3. Pure vs. mixed forests: Pure forests (P2) outperformed mixed forests (PC, PPC) in total carbon storage, driven by soil-layer contributions (>95% of total stocks). The 2 × 2 m pure forest (P2) demonstrated optimal carbon sequestration potential in the Qilian Mountains, with soil carbon dominance highlighting the importance of deep-layer SOC accumulation. While uneven-aged forests (PX) showed strong vegetation carbon storage, long-term carbon sinks require integrated soil management. These findings provide critical insights for arid-region plantation configurations. Future studies should combine remote sensing for dynamic carbon monitoring and explore diversified mixed-species systems to enhance ecosystem stability.